TRAINING OF ARTIFICIAL MEAT PROCESSING FROM SOYBEANS AS A SOURCE OF PROTEIN IN CADRES AND WOMEN GROUPS IN SYAHMAD VILLAGE, LUBUK PAKAM SUB-DISTRICT - bakara, tiar lince (Talenta Publisher Universitas Sumatera Utara, 2019)
Artificial meat has several features such as it can be formulated to have higher nutritional value than the original meat, more homogeneous, long-lasting storage (in dry condition), can be made without animal fat or cholesterol, contains a high content of unsaturated fatty acids which is good for health, and cheaper. The purpose of this community service activity was to improve the skills of cadres and women about the use of artificial meat from soybeans as a source of vegetable protein. The community service activity was conducted in the Syahmad District Office in Lubuk Pakam Sub-district which consisted of pre-intervention, intervention, and post-intervention activities. In the intervention stage, counseling and training in making artificial meat were carried out. The intervention results showed that PKK cadres and women groups were capable and skilled in making artificial meat and understood the benefits of artificial meat from soybeans as a source of protein. The artificial meat from soybeans can be a source of vegetable protein for health and reduce degenerative diseases.